EMPLOYMENT CONTRACT FORM - Ismoilov Shukhratjon Abdusaminovich (Scholar Express Journals, 2022)
This article examines the form of employment contract in Uzbekistan and other post-Soviet states, the main rules for its creation and formalization. The written, oral and electronic forms of the employment contract are studied through historical and comparative methods. In Uzbekistan, in addition to the written form of the labor contract, reasonable recommendations and suggestions have been put forward regarding the need to include its verbal and electronic forms in the labor legislation
Keywords: Employment contract; form of employment contract; oral; written